Effectiveness of Training and Use of Si Centing Application on Knowledge and Skills of Posyandu Cadres - Sinta Fitriani Fitriani; Amalia Siti Zahra; Ade Rahmat (Universitas Airlangga, 2022)
Background: Stunting is a condition where toddlers have a length or height that is less than their age. Various efforts have been made to overcome nutritional problems in the community through optimizing the role of posyandu. Cadres are front liners in the early detection of nutritional problems within the community, so they are required to have good knowledge and skills. Objective: The purpose of this study is to determine the effectiveness of the training and use of the Si Centing Application. Methods: This study used a pre-experimental design with a one group pretest-posttest design. The population in this study was all posyandu cadres with a total sample of 64 people. Data collection techniques were carried out by measuring the knowledge and skills of cadres before and after receiving training and using the centing application. The data analysis technique used the T-test. Results: The P-Value of the statistical knowledge test was 0.000 and the p-value for attitude was 0.000. These results indicate that H0 was rejected, so it can be concluded that there are differences in the average value of the knowledge and skills of volunteers before and after the training and use of the Centing application. Conclusion: There was a difference in the average value of knowledge and skills of cadres before and after the training and use of the Centing application in Singaparna District 2020. We suggest Puskesmas and Health to develop an agenda for capacity building activities for Posyandu cadres which are held regularly by using tools or promotional media of health according to the needs of the community.